KARAKTERISASI STRUKTUR TRITERPENOID DARI AKAR TANAMAN LANGSAT (Lansium domesticum) (CHARACTERIZATION OF TRITERPENOID STRUCTURE FROM LEAN PLANT (Lansium domesticum)) - Rizki Triadi; Rudiyansyah Rudiyansyah; Andi Hairil Alimuddin (Tanjungpura University, 2021)
Langsat root is a part of Lansium domesticum which is still rarely explored for its secondary metabolites. Triterpenoids are dominantly isolated from langsat plants. This research was conducted to isolate and characterize a triterpenoid structure by doing maceration and partition, phytochemical test, chromatography, and analysis of 1H-NMR spectrum. GKGT2 isolate is a white powder with a mass of 4 mg. 1H-NMR spectrum data (CD3OD, 500 MHz) shows an oxiran proton signal at H 4.13. The hydroxyl proton at C-1 with a chemical shift of 7.83 (1H, s) is a sharp singlet because a hydrogen bond strongly with the carbonyl at C-16. The presence of a singlet proton at H 5.85 (1H) and signals below 2 ppm are typical for terpenoid compounds. On the basis of a phytochemical test and chemical shift data in 1H-NMR spectrum, it can be concluded that a structure of GKGT2 isolate showed many similarities to Dukunolida C.